THE INFLUENCE OF DIGITALIZATION AND COMPETENCE ON EMPLOYEE PERFORMANCE WITH TRANSFORMATIONAL LEADERSHIP AS A MEDIATING VARIABLE AT THE NGANTANG DISTRICT OFFICE - Agus Priyono; Elevenson Nadapdap; Sunardi; Harsono (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to analyze the impact of digitalization and competence on employee performance, with transformational leadership as a mediating variable at the Ngantang District Office. Utilizing a quantitative research approach, data were collected through surveys from selected respondents. The study employs regression and path analysis to examine the relationships between variables. The findings indicate that digitalization and competence have a significant positive effect on employee performance, as they enhance efficiency, decision-making speed, and service quality. However, the successful implementation of digitalization depends on employees’ competency levels and the support of transformational leadership. Transformational leaders play a crucial role in motivating employees, fostering adaptability, and reducing resistance to digital transformation. The study highlights that transformational leadership partially mediates the relationship between digitalization, competence, and performance, meaning that leadership effectiveness can enhance the benefits of digital initiatives. The results support the Job Demands-Resources theory, emphasizing that a combination of technological advancements and strong leadership positively impacts employee performance. The findings provide practical implications for improving digital adoption strategies, developing competency-based training programs, and enhancing leadership approaches to optimize employee performance in public administration.